MOTIVASI PENCEGAHAN DENGAN KESIAPSIAGAAN SISWA MENGHADAPI KEJADIAN LUAR BIASA DEMAM BERDARAH DENGUE - NI LUH KOMPYANG SULISNADEWI; NI MADE AYU CINTYA DEWI; I NYOMAN RIBEK (Jurnal Gema Keperawatan, 2018)
Prevention Motivation With Student Preparedness Facing Extraordinary Events Dengue Hemorrhagic Fever. The purpose of this study to know the relationship of prevention motivation with student preparedness to face the extraordinary incidence of dengue hemorrhagic fever in SMP N 3 Ubud. This type of nonexperimental quantitative research with the correlational study. The approach used is cross-sectional. The sample used was 157 people taken using simple random sampling technique. The result of the analysis with the Spearman rank test got the value of r equal to 0,810 and p-value 0.000. This means that there is a preventive motivation relationship with student preparedness to face the extraordinary incidence of dengue hemorrhagic fever in SMP Negeri 3 Ubud with the direction of the positive relationship and strong relationship strength.